A call for a critical urban climatology: Lessons from critical physical geography. (10th March 2022) - Beray‐Armond, Núbia
Abstract: Urban climatology and environmental justice frequently share the same research site: the city. However, they study urban areas in distinct ways. Urban climatology has contributed to a better understanding of the urban boundary and canopy layer climates by embracing a broader and deeper investigation of the atmospheric and climatic specificities of the cities. Environmental justice has contributed a better understanding of how the poor and people of color are disproportionally affected by environmental problems. I argue here that we need both fields to fully understand urban climates because they are shaped both by legacies of colonialism, and race, gender, and class, and by the particularities of urban energy budgets and the variation in intra‐urban air quality and thermal‐hygrometric characteristics they drive. Critical physical geography can provide important analytical, theoretical, and methodological tools to help urban climatologists and environmental justice scholars work together toward the goal of social and environmental transformation. This article is categorized under: Climate, History, Society, Culture > Disciplinary Perspectives Climate and Development > Social Justice and the Politics of Development Abstract : Complexity of urban climates